Alam Semesta Menurut Tafsir Klasik dan Modern - Ruslan, Ruslan (Interdisciplinary Explorations in Research Journal, 2025)
The universe has been described in various ways. Medieval naturalists called it the Great Universe, and the universe around us is called the Universe. If the Quran calls it al-sama wa al-syamawat, then, in context, it could mean the sun, moon, stars, astroids, interstellar matter, the atmosphere, matter, and others, including our earth, as well as various forms of catastrophe (katastropik) and scattering effects (the scattering of sunlight). The basic material of the universe is al-dukhn (smoke/hydrogen), and it develops over six days Monday, Tuesday, Wednesday, Thursday, Friday, and Saturday ), or six periods. It then continues to expand until it contracts again due to the exhaustion of its gravitational center. In the hadith, "qabadha bi yaminihi" means "God grasped it with His right hand," or according to the Quran, كطى السجل للكتب kathayyis sijjil li al-kutub" means "like From the perspective of the source, the first material is linguistic and Islamic cosmology. From the methodological perspective, it falls under tafsir bi al-udzwi (a combined exegesis between narrative tafsir and analytical tafsir).